The Perspective of Women’s Hakiki Justice: New Methods in Gender Based Research - Misbah Hudri (Al-'Allāmah: Journal of Scriptures and Ulama Studies, 2025)
This Women's hakiki justice was initiated by Nur Rofiah, is a perspective in gender-based research. This perspective is one of three offered by the Kongres Ulama Perempuan Indonesia. The basic principle is that justice does not make the strong and dominant standard for the weak and vulnerable. By looking at women's unique experiences, namely biological experiences (menstruation, pregnancy, giving birth, childbirth, and breastfeeding) and social experiences (stigmatization, marginalization, subordination, violence, and double burden). Women can only obtain hakiki justice if it is addressed by ensuring five biological experiences are facilitated and five social experiences are eliminated. This type of research is included in qualitative research by processing library data using descriptive-analytical methods. Briefly reviews the perspective of Women's Hakiki Justice, a new way of reading in gender research. One of the examples raised is the concept of marriage in QS. ar-Rum (30): 21. Women's hakiki justice as a perspective is still trying to find ways that are more detailed and more concrete steps. But, at least this perspective of hakiki justice offers new things that are more gender-just. In addition, it also introduces three types of verses in the Qur'an, namely the starting point verse, the intermediate target verse, and the final destination verse as an effort to arrive at Islamic ideals. Furthermore, as an example of application from the perspective of women's hakiki justice, which departs from the concept of marriage. Then it is supported by other elements such as how samawa in marriage, a shared goal, can be realized and create mutual benefit. Demanding peace, love, and compassion between the two parties and happiness both. This includes the perspective of hakiki justice that is not in line with polygamy or wife beating. The intended marriage emphasizes that the two are in a pair relationship, making the marriage a solid promise between husband and wife to Allah. Then build a relationship that is dignified, fair and mutually pleasing between the two.